If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 3 = 2(5x + -2) + 7 Reorder the terms: 3 + 11x = 2(5x + -2) + 7 Reorder the terms: 3 + 11x = 2(-2 + 5x) + 7 3 + 11x = (-2 * 2 + 5x * 2) + 7 3 + 11x = (-4 + 10x) + 7 Reorder the terms: 3 + 11x = -4 + 7 + 10x Combine like terms: -4 + 7 = 3 3 + 11x = 3 + 10x Add '-3' to each side of the equation. 3 + -3 + 11x = 3 + -3 + 10x Combine like terms: 3 + -3 = 0 0 + 11x = 3 + -3 + 10x 11x = 3 + -3 + 10x Combine like terms: 3 + -3 = 0 11x = 0 + 10x 11x = 10x Solving 11x = 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 11x + -10x = 10x + -10x Combine like terms: 11x + -10x = 1x 1x = 10x + -10x Combine like terms: 10x + -10x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 5/6x+4/3=5 | | 21z^3+28z=0 | | 4x+(3x+5)= | | -6x+x^2+3=100-10y-y^2 | | -8r+7+9r=26 | | b(2)-7r+10=0 | | 6y-(10y-3y)=2 | | 3x+2y/3x+y | | x^2+14x+y^2=-4+12y | | 28v^2+16v-44= | | 7x^2-x=7 | | x^2-21x+69=0 | | x^2+10x+87=0 | | 6(7-10x)+3(3-15x)=366 | | 15b^2+25b-40= | | -0.66666666666667x=0.83333333333333 | | -21x^2+95x+6=0 | | 9y+2(6y-5)=53 | | 2x+3c+x+c= | | r(2)-7r+10=0 | | 5x^2-18xy-8y^2= | | (3x)+(x+8)=180 | | 9y+9(14y+2)=288 | | f(x)=6x^2+13x+6 | | 2(x-1)=x-4 | | -8x+5y=7 | | x(2)-x=0 | | 2x^2+3x-7=x^2+5x+39 | | 3(p+9)-12p=51 | | 6-6x+3x=-21 | | 11p=22 | | 5x+10+11x+2+58=360 |